Belonging through values: ethical leadership, creativity, and psychological safety with ethical climate as a moderator - Qasim, Muhammad; Laghari, Azhar Ali (Frontiers in Psychology, 2025)
IntroductionThis study aims to provide conceptual insights on how varying levels of value congruence vary employees’ sense of belongingness within ethically led organizations. The ethical leadership effect was tested directly and indirectly through belongingness and psychological safety on creativity; the ethical climate was considered as a moderator.MethodsStudy 1 data was multi-sourced and was collected from 377 participants at three different time points. Study 2 was scenario-based data collection. 208 employees participated in this study. The process and Hayes techniques were used for SPSS.ResultsFindings were that ethical leadership was a significant factor in influence directly and indirectly through belongingness and psychological safety on creativity; the moderating role of ethical climate was also found significant. Belongingness varies at high and low levels of congruency with the leader.ConclusionFindings suggest that ethical leadership is a strong predictor of belongingness and psychological safety that helps employees to be creative. Overall, the working climate, if it is ethical, also improves the impact of ethical leadership. Then, it discusses the theoretical and practical implications of ethical leadership for research and practices.